ATP synthase promotes germ cell differentiation independent of oxidative phosphorylation. - Teixeira, F.K.; Sanchez, C.G.; Hurd, T.R.; Seifert, J.R.; Czech, B.; Preall, J.B.; Hannon, G.J.; Lehmann, R. (Nature Cell Biology, 2015)
The differentiation of stem cells is a tightly regulated process essential for animal development and tissue homeostasis. Through this process, attainment of new identity and function is achieved by marked changes in cellular properties. Intrinsic cellular mechanisms governing stem cell differentiation remain largely unknown, in part because systematic forward genetic approaches to the problem have not been widely used. Analysing genes required for germline stem cell differentiation in the Drosophila ovary, we find that the mitochondrial ATP synthase plays a critical role in this process. Unexpectedly, the ATP synthesizing function of this complex was not necessary for differentiation, as knockdown of other members of the oxidative phosphorylation system did not disrupt the process. Instead, the ATP synthase acted to promote the maturation of mitochondrial cristae during differentiation through dimerization and specific upregulation of the ATP synthase complex. Taken together, our results suggest that ATP synthase-dependent crista maturation is a key developmental process required for differentiation independent of oxidative phosphorylation.